Heavy Metals, Wastewater Pollution, and Ecological Risks in the Euphrates River of Dhi Qar Province, Iraq: A Comprehensive Review - Salih, Hayder Zamil Khazaal Albu (American Journal of Biology and Natural Sciences, 2026)
The extreme aggregation of burdensome metals and pollutants from waste wholes are chief to weighty adulteration of freshwater resources, happening in harm to the atmosphere and society. The Euphrates is individual of ultimate valuable water sources in Iraq, that is handled for household, land and industrial needs. However, in current age on account of hasty urbanisation, farming and industrial incident, and incompetent wastewater administration, the characteristic of the water has endured in some parts ahead penal institution. In this review, the closeness, allocation and tangible effects of severe metals and waste befriended contaminators of the Euphrates waterway in Dhi Qar Province, Iraq was assessed. Evidence desires various metals to a degree iron (Fe), manganese (Mn), lead (Pb), cadmium (Cd), metallic mineral (Zn), planets orbiting sun (Hg), arsenic (As), chromium (Cr), and nickel (Ni) have happened discovered in surface water and sediments at levels that now and then are above urged environmental directions. Sewage-carried contaminators like food salts, pharmaceuticals and microbial markers again are main water feature stressors and contaminants. Physicochemical possessions that could impact contaminator flexibility, relating to space and worldly alternatives in concentration of contaminators, and potential belongings of contaminators to maritime animals and humans too are examined. The tangible risk amount (tangible risk index, Hazard Quotient) indicates weighty environmental concerns from few of the contaminators (Pb, Cd, Cr and As) in fields of high urbanization and machine control. The determinants that were establish to influence contaminator transport and allocation were seasonal changes, hydrological environments, and land use. The overall verdicts imply that the need for more joined approaches for managing water status, routine preservation of natural resources, revised wastewater situation facilities and upgraded referring to practices or policies that do not negatively affect the environment government to weaken dirtiness and ensure the environmental well-being of the Euphrates River. These are owned by guarantee sustainability of the freshwater possessions of the southern indiscriminate Iraq and to safeguard the environment and human fitness.